2020
DOI: 10.1186/s10086-020-01927-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal insulation and hydrophobization of wood impregnated with silica aerogel powder

Abstract: The aim of the study was to develop a simple and cost-effective method to improve thermal insulation and hydrophobicity of wood. Herein, we attempted to use commercially available silica aerogel powders suspended in ethanol to treat the wood by a simple vacuum impregnation process. The effects of particle size (20 µm and 40 nm) of silica aerogels and the number of impregnation cycles (1, 3, and 5 cycles) were examined on the thermal conductivity and the surface hydrophobicity. The results showed that the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…A very strong linear relationship between contact angle and aerogel content was observed. This could be mainly due to the introduction of the strong hydrophobic silica aerogel and the gradual increase in the number of hydrophobic groups present on the aerogel surface, which agrees well with previous studies [ 35 , 36 , 37 ]. In addition, the hydrophobicity of the electrosprayed materials strongly relied on surface roughness, which varied when different contents of aerogels were applied as mentioned above.…”
Section: Resultssupporting
confidence: 92%
“…A very strong linear relationship between contact angle and aerogel content was observed. This could be mainly due to the introduction of the strong hydrophobic silica aerogel and the gradual increase in the number of hydrophobic groups present on the aerogel surface, which agrees well with previous studies [ 35 , 36 , 37 ]. In addition, the hydrophobicity of the electrosprayed materials strongly relied on surface roughness, which varied when different contents of aerogels were applied as mentioned above.…”
Section: Resultssupporting
confidence: 92%
“…Nanomaterials are the most popular modified materials in recent years [ 19 ] and have been applied to many modifiers, such as paints [ 20 , 21 ], wood, etc. It has been confirmed that nano-SiO 2 can improve the mechanical properties of wood [ 22 , 23 ] and dimensional stability [ 24 ], and some scholars have also used SiO 2 to improve the hydrophobicity and thermal insulation of wood [ 25 ]. Inspired by these aspects, in this study, nano-SiO 2 was added to the urea-formaldehyde resin to impregnate the fast-growing poplar, and the integrated technology of impregnation enhancement and high-temperature heat treatment was used for modification.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the interior decoration of buildings becomes a system project that can o er a number of decorative materials and products [2]. At the same time, they can be customised and produced according to the needs and environmental requirements of the user in order to create a perfect artistic space [3]. It is a cross-regional, cross-sectoral, multi-product, high-technology emerging industry.…”
Section: Introductionmentioning
confidence: 99%